Aggressive Posterior Retinopathy of Prematurity (APROP), timely screening and appropriate treatment - Case Report - Isjanovski, Igor; Gjoshevska Dashtevska, Emilija; Stojanovska, Andrea (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2025)
Retinopathy of prematurity (ROP) is a vasoproliferative disease of the retina that is one of the leading causes of blindness in children. In this paper, we describe a case of a premature male child diagnosed with a aggressive posterior form of ROP (APROP) and treated with anti- VEGF injections in both eyes. Ophthalmological monitoring was done during several years of the child's growth. The aim is to highlight the importance of timely screening protocols in order to prevent permanent consequences on visual acuity.
ЗАДНА АГРЕСИВНА ПРЕМАТУРНА РЕТИНОПАТИЈА (APROP), НАВРЕМЕН СКРИНИНГ И СООДВЕТЕН ТРЕТМАН - ПРИКАЗ НА СЛУЧАЈ
Keywords: retinopathy of prematurity (ROP); anti-VEGF; screening; visual acuity; APROP